HUBUNGAN SANITASI FISIK RUMAH DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA DI PUSKESMAS KARO KELURAHAN KARO PEMATANGSIANTAR - Samuel Marganda Manalu; Cindy Avrilta Sembiring (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
The objective of this research is to find out the environment health housing that influencing the numbers of upper respiratory tract infection incidence in children under 5 years old in puskesmas karo. The research was 67 children under 5 years old. Result of this study showed the upper respiratory tract infection incidence in children under 5 years old was 52,2 percent. Over crowed of the room, type of wall and room ventilation had the significant influence to the upper respiratory tract infection incidence of the children under 5 years.